French museums participate in Beijing’s erasure of Tibetan identity - Filip Noubel; Choekyi Lhamo (Global Voices, 2024)
Two major Paris museums are using terms other than “Tibet” to describe parts of their Tibetan cultural artifacts collections, thereby aligning themselves with Beijing’s policy of cultural erasure.
China